THE FREQUENCY OF GADGET USAGE OR MONITOR EXPOSURE AND EYESTRAIN - Suwarsi, Suwarsi; Rizqi, Januar; Wahyuningsih, Melania (Universitas Respati Yogyakarta, 2020)
Monitor exposure from laptops or computers, cellphones and the frequency of their use, is still a suspected cause of eye disorders. The impact felt by students from monitor exposure is the appearance of eye fatigue, which results in impaired concentration and focus of learning. This study was conducted to examine the causes of eye fatigue caused by the duration, distance, time and lighting in the use of gadgets, monitor exposure. This type of the study is quantitative with an analytic observational design. The sample technique used consecutive sampling. The sample in this study was 118 Nursing students at Respati University, Yogyakarta The Bivariate test used independent T-test. The results of the study showed that the eye fatigue of students was 92.4%. The relationship test of time, distance, time, and lighting in the use of gadgets with eye fatigue obtained p value more than 0.05. The relationship between the use of eye glasses and eye fatigue was 0.008 (p value < 0.05. There are no significant different between length, distance, time and lighting in gadget use and monitor exposure and eye fatigue. There is a significant different between the used of eye glasses and eye fatigue.